2023
DOI: 10.1177/08862605231153877
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Person-Centered and Cumulative Risk Approaches in Explaining the Relationship Between Adverse Childhood Experiences and Behavioral and Emotional Problems

Abstract: Adverse childhood experiences (ACEs) commonly co-occur, and researchers often estimate their impact using a cumulative risk approach. The person-centered approach offers another approach to operationalize the co-occurrence of ACEs. This study aims to estimate latent classes of ACEs in a sample of U.K. children, examine their relationship with emotional and behavioral problems, and compare the explanatory value of the latent classes to cumulative risk scores. Data were collected among a general population sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Current media and academic circles focus on the causes of, and solutions to, violence in school bullying, little attention is paid to its long-term impact on the physical and mental health and psychological experiences of victims. 19,20 This study aimed to explore the real inner experience and nursing needs of adolescent patients who suffered from school bullying, and to develop a treatment plan to restore adolescent mental health. Based on the real experiences of adolescent patients with mental disorders caused by school bullying (including mood disorders, anxiety disorders, trauma and stress related disorders, substance related disorders, mania et al), qualitative research methods were used to study the psychological experiences and nursing requirements of adolescent patients to provide a pertinent reference and guidance for the implementation of related nursing measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current media and academic circles focus on the causes of, and solutions to, violence in school bullying, little attention is paid to its long-term impact on the physical and mental health and psychological experiences of victims. 19,20 This study aimed to explore the real inner experience and nursing needs of adolescent patients who suffered from school bullying, and to develop a treatment plan to restore adolescent mental health. Based on the real experiences of adolescent patients with mental disorders caused by school bullying (including mood disorders, anxiety disorders, trauma and stress related disorders, substance related disorders, mania et al), qualitative research methods were used to study the psychological experiences and nursing requirements of adolescent patients to provide a pertinent reference and guidance for the implementation of related nursing measures.…”
Section: Introductionmentioning
confidence: 99%
“…Current media and academic circles focus on the causes of, and solutions to, violence in school bullying, little attention is paid to its long-term impact on the physical and mental health and psychological experiences of victims. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, important to further investigate the co-occurrence of different types of adversities among children and the resulting developmental outcomes, both of which could contribute to more effective interventions. Person-centered methods such as latent class analysis (LCA) are ideal for identifying common patterns of exposure and then tracking the psychiatric and behavioral outcomes of those patterns . For example, using data from the Fragile Families Child Well-being Study, Wang et al analyzed 10 adversities (eg, domestic violence, parental separation, and financial difficulties) at age 3 years using LCA to examine their associations with later internalizing and externalizing symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Person-centered methods such as latent class analysis (LCA) are ideal for identifying common patterns of exposure and then tracking the psychiatric and behavioral outcomes of those patterns. [23][24][25][26][27][28] For example, using data from the Fragile Families Child Well-being Study, Wang et al 29 analyzed 10 adversities (eg, domestic violence, parental separation, and financial difficulties) at age 3 years using LCA to examine their associations with later internalizing and externalizing symptoms. They found that children exposed to certain patterns of adversities, especially financial difficulty and child maltreatment (eg, psychological abuse, physical abuse, and neglect), exhibited more internalizing and externalizing behaviors at ages 5, 9, and 15 years than children exposed to low adversity.…”
mentioning
confidence: 99%
“…Many studies show that more than half of individuals have experienced at least one ACE (Esaki and Larkin 2013;Felitti et al 1998;Hales et al 2023;Manyema et al 2018;Merrick et al 2017;Nevárez-Mendoza and Ochoa-Meza 2022;Soares et al 2022). The most common types of ACEs are emotional abuse (67-82.9%) (Amaranggani and Dewi 2022;Goodman et al 2022), emotional neglect (60-82.2%) (AlHemyari et al 2022;Craig et al 2023), parental separation or divorce (42-77.6%) (Martin et al 2022;Soares et al 2016), and substance abuse in the household (25.6-31.6%) (Felitti et al 1998, Nevárez-Mendoza andOchoa-Meza 2022).…”
Section: Introductionmentioning
confidence: 99%